Strategies for college writing sentences, paragraphs, essays - Harris, Jeanette 1936-; Moseley, Ann (2004)
Teaching students to write effective paragraphs and college essays and how to respond in writing to academic readings, this book provides a review of sentence, grammar, and punctuation skills. Emphasis is on the importance of the controlling idea, information gathering, paragraph and essay structure, arranging and connecting ideas, and revision.